Social Proof and Urgency Scarcity can Mediate The Influence of Tiktok Ads on Purchasing Decisions - Hendrik Permana; Rainier Hendrik Sitaniapessy; Nurul Septya Magisa; Rizaldy Rizaldy; Sintya Purwandaningsih (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of the social commerce ecosystem has transformed digital consumer behavior, with social media platforms like TikTok shifting towards direct transaction generation. This study aims to empirically analyze and prove the mediating role of Social Proof and Urgency Scarcity in the influence of TikTok Ads on consumer Purchasing Decisions. Employing an explanatory quantitative approach, data were gathered via a structured online questionnaire administered to 285 active consumer respondents who had previously purchased products through the TikTok platform. The sampling technique utilized purposive sampling, and the collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. The empirical findings reveal that TikTok Ads have a direct, positive, and significant effect on Social Proof, Urgency Scarcity, and Purchasing Decisions. Furthermore, mediation analysis confirms that both Social Proof and Urgency Scarcity significantly mediate the relationship between TikTok Ads and consumer Purchasing Decisions. Social Proof acts as a driver of psychological trust and social validation, whereas Urgency Scarcity triggers an emotional push through the Fear of Missing Out (FOMO), accelerating the purchase execution process. Practical implications suggest that digital marketers should design TikTok advertising strategies that extend beyond visual appeal by ethically integrating authentic social proof and time-sensitive scarcity triggers to maximize sales conversion rates.